First sign of native valve endocarditis in the COVID-19 pandemic: Acute arterial septic embolism in the lower extremity - Cengiz Bolcal; Gökhan Erol; Tuna Demirkıran; Murat Kadan; Emre Kubat (Genel Tıp Dergisi)
he clinical manifestations of infective endocarditis are variable. Late diagnosis of the disease can lead to clinical catastrophe and even death. Although its symptomatology is broad, the initial diagnosis can sometimes be made after complications, particularly during COVID-19 pandemic days. It should be noted that during the pandemic period, patients with mild infective endocarditis symptoms may be confused with covid 19 infection symptoms. In this report, we aim to present that lower extremity ischemia was the first sign of infective endocarditis in a 77-year-old female patient with complaints of sudden onset of pain and coldness in the leg. The patient underwent an embolectomy and embolic material of 1x1.5 cm was removed from the left common femoral artery.